Delayed Hypersensitivity Reaction after Nipple Tattooing: A Novel Case Report. Issue 9 (September 2019) - Joseph, Walter J.; Roy, Eva; Stofman, Guy M.
Abstract : Summary: We present a patient who underwent bilateral 3-dimensional (3D) nipple tattooing for nipple areolar reconstruction after implant-based breast reconstruction for breast cancer. Several weeks after nipple tattooing, the patient developed a delayed hypersensitivity reaction around both of her tattooed nipple areolar complexes. This is the first case reported in the literature of a hypersensitivity reaction from 3D nipple tattooing.